Unilateral Re-Expansion Pulmonary Edema following Treatment of Pneumothorax with Exceptionally Massive Sputum Production, followed by Circulatory Collapse. Issue 2 (2010) - Komatsu, Teruya; Shibata, Sumiya; Seo, Ryutaro; Tomii, Keisuke; Ishihara, Kyousuke; Hayashi, Takurou; Takahashi, Yutaka
Abstract : A case of a 61-year-old man who developed ipsilateral re-expansion pulmonary edema after pleural drainage for a right pneumothorax is described. The patient's chest x-ray revealed a totally collapsed right lung. After insertion of a chest drainage tube, he began to produce a moderate amount of serous, yellowish sputum. Despite continuous positive airway pressure support, his dyspnea gradually worsened and his oxygenation could not be maintained; therefore, to improve his hypoxemic state, intubation was necessary. His chest x-ray following chest tube insertion showed ipsilateral diffuse infiltrates. These radiographic and physical findings were consistent with re-expansion pulmonary edema. The present case was complicated by extreme hypotension and tachycardia due to massive fluid loss. His condition gradually improved with invasive mechanical ventilation. Re-expansion pulmonary edema is an uncommon complication of pleural drainage for pneumothorax, and therapy is supportive. In the present case, the exceptional severity of the pulmonary edema, as well as its general concept, is reviewed in accordance with other relevant literature.